In vitro anti-inflammatory, mutagenic and antimutagenic activities of ethanolic extract of Clerodendrum paniculatum root - Pravaree Phuneerub; Wacharee Limpanasithikul; Chanida Palanuvej; Nijsiri Ruangrungsi (Wolters Kluwer Medknow Publications, 2015)
Clerodendrum paniculatum L. (Family Verbenaceae) has been used as an antipyretic and anti-inflammatory drug in traditional Thai medicine. This present study investigated the in vitro anti-inflammatory, mutagenic and antimutagenic activities of the ethanolic extract of C. paniculatum (CPE) dried root collected from Sa Kaeo Province of Thailand. Murine macrophage J774A.1 cells were stimulated by lipopolysaccharide (LPS) to evaluate nitric oxide (NO), tumor necrosis factor-α (TNF-α) and prostaglandin E 2 (PGE 2 ) production in the anti-inflammatory test while the mutagenic and antimutagenic potential was performed by the Ames test. The outcome of this study displayed that the CPE root significantly inhibited LPS-induced NO, TNF-α, and PGE 2 production in macrophage cell line. In addition, the CPE root was not mutagenic toward Salmonella typhimurium strain TA98 and TA100 with and without nitrite treatment. Moreover, it inhibited the mutagenicity of nitrite treated 1-aminopyrene on both strains. The findings suggested the anti-inflammatory and antimutagenic potentials of CPE root.